2021
DOI: 10.3390/en14154484
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Persistence, Non-Acceptance and Sufficiency in Long-Term Energy Scenarios for Germany

Abstract: Long-term transition pathways to a low-carbon energy system are analysed by applying the energy system model REMod. All in all, the paper contributes to the current research through an innovative scenario approach, using assumptions for societal trends and quantitative results for scenarios, analysing the paths towards climate neutrality and defossilization in 2050. In the case study of Germany, these trends and drivers influence the results and the technology composition in each consumption sector (buildings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…For the goal of the consistency strategy of a 100% renewable energy supply, efficiency plays a major role in form of flexibility, to efficiently integrate the fluctuation of solar and wind energy [7]. As summarized by [8], absolute emission reductions are limited by economic growth and the rebound effect.…”
Section: Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…For the goal of the consistency strategy of a 100% renewable energy supply, efficiency plays a major role in form of flexibility, to efficiently integrate the fluctuation of solar and wind energy [7]. As summarized by [8], absolute emission reductions are limited by economic growth and the rebound effect.…”
Section: Efficiencymentioning
confidence: 99%
“…recycling is a form of consistency improvement, while only a complete circularity agrees with zero resource input and is respecting the finity of resources and the environmental impacts of their extraction. The limitations of consistency are assigned to the uncertainty of technological optimization and global justice [8], underlining the need of sufficiency considerations.…”
Section: Consistencymentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptance of the local population is a considerable condition for the realization of energy projects and thereby for meeting energy policy goals. Energy transition scenarios with a high degree of non-acceptance of new technologies by the population can significantly halt the reaching of carbon-neutral energy systems and increase energy import dependencies [7]. Resistance from the population repeatedly led to considerable delays and the need to re-plan projects [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on optimal investments at a national level which consider a variety of potentials, e.g., [3][4][5], found that both RE and complementing flexibility investments are necessary for cost-effective and sustainable decarbonization efforts. Studies at an end-user level are sparse and often focus of selected technologies or applications.…”
Section: Introductionmentioning
confidence: 99%